FRI0185 Are There Differences in Baseline Characteristics of Patients with Rheumatoid Arthritis Treated with Tumor Necrosis Factor Inhibitors According To The Presence of Comorbidities?. (15th July 2016) - Hernández, M.V.; Sánchez-Piedra, C.A.; Gόmez-Puerta, J.A.; Sánchez-Alonso, F.; Manero-Ruiz, J.; Cuende, E.; Rosello Pardo, R.; Perez-Pampin, E.; Rodriguez-Lozano, C.; Sanmartí, R.; Gόmez-Reino, J.J.; ,
Abstract : Background: Rheumatoid arthritis (RA) is often associated with comorbidities that may affect the therapeutic choice or a different management in clinical practice. It is unclear whether patients with comorbidities have a different profile from those without Objectives: To analyze differences in the baseline characteristics of RA patients treated with tumor necrosis factor inhibitors (TNFi) according to the presence or not of concomitant comorbidities Methods: All patients from the BIOBADASER 2.0 register with a diagnosis of RA treated with TNFi from January 2008 to December 2014 were selected and divided into 2 groups according to the presence or not of comorbidities. Comorbidity was defined as ≥1 of the following at initiation of TNFi: ischemic heart disease; malignancy; diabetes; chronic pulmonary obstructive disease; smoking; hypercholesterolemia; hypertension; heart failure; renal failure; osteoporosis; Epstein Barr, hepatitis B or C virus infection; and others. Variables analyzed were: age; gender; disease duration; disease activity at initiation of biological therapy measured by the DAS-28 score; number of previous biological agents (0, 1, ≥2); concomitant glucocorticoids or synthetic DMARD; and biological duration. Differences between groups were analyzed Results: From January 2008 to December 2014, 640 RA treated with TNFi were included in the BIOBADASER 2.0 register. Baseline characteristics are shown in Table 1 . Patients with associated comorbidities were significantly older, less frequently female, had received a higher number of previous biologics, and had a higher baseline DAS-28 compared with patients without comorbidities Conclusions: RA patients treated with TNFi with baseline comorbidities are significantly older, have a higher baseline DAS 28 and had received more previous biologics, suggesting a RA population with higher activity than those without comorbidities. Whether this higher baseline activity favors the development of comorbidities, or whether comorbidities limited therapy in these patients, requires analysis. Disclosure of Interest: None declared